ANALISIS KEBUTUHAN FUNGSIONAL APLIKASI PENANGANAN KELUHAN MAHASISWA STUDI KASUS: STMIK ROSMA KARAWANG - Lila Setiyani; Evelyn Tjandra (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2021)
In the current era of globalization, the very rapid development of information technology cannot be avoided, one of which is in the world of education. Global demands require the education sector to constantly adjust technological developments with efforts to improve the quality of education, adjust the use of information and communication technology. STMIK Rosma is a university that uses computer technology. However, there are still deficiencies, namely the absence of a student complaint handling application so that there is no time efficiency in submitting student complaints, no data on student complaints, and staff cannot document complaints that have been resolved, and the university leadership of the campus cannot monitor student complaints. STMIK Rosma has difficulties in handling student complaints because there is no computational process in the complaint handling process. This resulted in poor handling and decreased performance because the handling was still manual so that it was no longer effective in handling complaints. This study aims to analyze the functional requirements of the application for handling complaints of STMIK Rosma students. The method used in this study uses PIECES (Performance, Information, Economy, Control, Efficiency and Service). The results of this study, based on the problems that the root of the problem has been identified, are based on the input and output processes and their solutions, which are the basis for producing an analysis of functional requirements needed in building student complaint handling applications.